2018
DOI: 10.1111/ijcp.13096
|View full text |Cite
|
Sign up to set email alerts
|

Establishing a proactive geriatrician led comprehensive geriatric assessment in older emergency surgery patients: Outcomes of a pilot study

Abstract: Proactive geriatrician input identifies medical diagnoses and geriatric syndromes missed by the surgical teams. Managing these issues has contributed to a reduced length of stay in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 25 publications
0
10
1
Order By: Relevance
“…We found that geriatricians performed more poorly on cost and quality measures than other PCPs, although a substantial portion of these differences were explained by frailty and neuropsychological conditions, as noted above. This is in contrast to prior literature that has demonstrated generally better outcomes for older adults cared for by geriatricians compared to other clinicians . A potential reason is residual confounding.…”
Section: Discussioncontrasting
confidence: 89%
“…We found that geriatricians performed more poorly on cost and quality measures than other PCPs, although a substantial portion of these differences were explained by frailty and neuropsychological conditions, as noted above. This is in contrast to prior literature that has demonstrated generally better outcomes for older adults cared for by geriatricians compared to other clinicians . A potential reason is residual confounding.…”
Section: Discussioncontrasting
confidence: 89%
“…Various measures of frailty correlate with various outcomes, including postoperative morbidity and mortality, intensive care survival and postdischarge status . There is some evidence that specialist frailty assessment and treatment teams might alter outcomes . The classification of patients by ASA physical status is similar to their classification by functional frailty.…”
Section: Alternative Scoring Systemsmentioning
confidence: 99%
“…Multidisciplinary teams including geriatricians along with surgeons and anesthesiologists have been established so far in the orthogeriatric field, but there are very scant evidence on the effectiveness of such teams in oncological surgery [43][44][45][46]. Yet, we predict that, once established, such teams will successfully improve many clinical outcomes associated with solid tumor and their surgery, improving patient's functional status and quality of life.…”
Section: The Geriatrician's Clinical Standpointmentioning
confidence: 99%